Offline/online brand element transmutation and tangible/intangible product characteristics within various South African retail brand categories: An exploratory study - H. Kruger; L. C.H. Fourie; N. S. Terblanche (South African Journal of Business Management, 2005)
The aim of this study is firstly to investigate if offline/online brand transmutation (uniform/non-uniform) patterns are particular to certain retail categories. Secondly, to determine if product characteristics (tangibility/intangibility; high cost, low frequency/low cost, high frequency; high potential for differentiation/low potential for differentiation) and brand transmutation is dependent or independent. Thirdly, given a particular product characteristic and brand transmutation is dependent, to establish the significance of the dependence effect. Two hundred and eleven South African retailers, divided into sixteen categories were surveyed. Structured observation was used as data collection method and surveyed data was analysed using quantitative methods, namely classification tree analysis and the Fisher exact test supported by the log linear model. The results in the first instance indicated with very strong statistical significance that uniform/nonuniform brand transmutation is retail category specific. Secondly, at a five percent level of significance that the factors product characteristic tangibility/intangibility and uniform/non-uniform brand transmutation are dependent. Thirdly, at a one percent significance level, that different factor effects are of relative importance. The product characteristic tangibility/intangibility is the most important factor in offline/online brand element transmutation. Brand element transmutation is more important than the effect of the two factors. However, the factors and the effects are of high statistical significance and play a role in offline/online brand element uniformity/non-uniformity. The implication of this result is that products with tangible characteristics should be uniform offline and online, and commensurately products with intangible characteristics should be non-uniform offline and online. This may be explained by the inherent unsuitability of the Internet as distribution channel for tangible products and thus the risk reduction exercise in keeping the brand uniform offline/online.
Keywords: 650